The New Possibilities of Dynamic Compensation and Regeneration of Energy in Electric Traction - Dobrucky, Branislav; Otcenasova, Alena; Pokorny, Michal; Tabacek, Rastislav (Communications - Scientific letters of the University of Zilina, 1999)
The paper presents dynamic compensation, harmonics filtration and regeneration of symmetrical non-harmonic / non-linear loads in energetic systems. The new original thought uses Clarke’s orthogonal transform for creation of state-space vector of investigated quantities and its decomposition into real- and imaginary components. The acquisition and control circuitry of the filter can then handle fast dynamic changes of the load, due to six-side symmetry of state-space vector in the complex domain. The analysis and computation of the load’s active power / current should be completed within one fourth of the period for single-phase system and one sixth of the period for threephase system (from acquired data of previous fourth or sixth periods). The compensator response to the actual state of the load then can be as fast as possible.